Food Insecurity and the Unsustainable Hunting of Wildlife in a UNESCO World Heritage Site - Borgerson, Cortni; Razafindrapaoly, BeNoel; Rajaona, Delox; Rasolofoniaina, Be Jean Rodolph; Golden, Christopher D. (Frontiers in Sustainable Food Systems, 2019)
Madagascar faces dual challenges in biodiversity conservation and public health. In order to identify strategies to reduce the unsustainable hunting of threatened species while maintaining or improving child nutrition, we quantified interactions among ecosystem indicators (lemur density and habitat biodiversity indices), health indicators (stunting, underweight, wasting, and anemia), nutrition, food security, and wildlife hunting through interviews of 1,750 people in 387 households and surveys of 28 wildlife transects with 156 habitat plots at 15 sites on Madagascar's Masoala Peninsula, a UNESCO World Heritage Site. The surveyed population ate 6,726 forest animals (mammals and birds), or a mean of 3.27 kg of wild meat per person (4.48 kg per adult equivalent) during the prior year. Local Malagasy were also highly food insecure (78% of households) and malnourished (for children under five, as many as 67% were stunted, 60% were underweight, 25% were wasted, and 40% were anemic). In some communities, nearly 75% of animal-sourced calories, 76% of protein, and 74% of iron came from forest animals-demonstrating a strong dependence on wild foods. Few micronutrient-rich alternatives to wild meats were available in adequate supply and many were highly volatile; for example, 79% of chickens died from Newcastle disease in the prior year. The survivorship of lemurs (94% of lemur species are threatened with extinction) depends on providing food security to a malnourished human population who commonly hunts wildlife for food. Currently, wildlife provides a critical source of micronutrients, yet the hunting of threatened species is an untenable solution to poor diet and food insecurity. Given the established connection between wild foods and human nutrition, reductions in forests and wildlife populations will also threaten the local food supply. In order to reduce the unsustainable hunting of threatened species while improving household food security and child health, we suggest testing the effects of increasing the affordability, accessibility, and stability of micro-nutrient rich animal-sourced foods in communities where forests contribute the most to food security.